2020
DOI: 10.1111/pce.13810
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress and fluctuating light have separate effects on photosynthetic acclimation, but interactively affect biomass

Abstract: In nature, soil salinity and fluctuating light (FL) often occur concomitantly. However, it is unknown whether salt stress interacts with FL on leaf photosynthesis, architecture, biochemistry, pigmentation, mineral concentrations, as well as whole-plant biomass. To elucidate this, tomato (Solanum lycopersicum) seedlings were grown under constant light (C, 200 μmol m −2 s −1) or FL (5-650 μmol m −2 s −1), in combination with no (0 mM NaCl) or moderate (80 mM NaCl) salinity, for 14 days, at identical photoperiods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 58 publications
(113 reference statements)
3
31
0
5
Order By: Relevance
“…Using scanning electron microscopy, we further showed that stomatal opening instead of stomatal density was affected after 7 days of FL treatment (Figure 5e–j, Table S7). Some researchers reported that after longer FL treatment (14 days of FL), stomatal density, size and aperture were all reduced (Zhang et al, 2020). Therefore, the regulation of stomatal opening is an early response to FL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using scanning electron microscopy, we further showed that stomatal opening instead of stomatal density was affected after 7 days of FL treatment (Figure 5e–j, Table S7). Some researchers reported that after longer FL treatment (14 days of FL), stomatal density, size and aperture were all reduced (Zhang et al, 2020). Therefore, the regulation of stomatal opening is an early response to FL.…”
Section: Discussionmentioning
confidence: 99%
“…These results show the importance of manipulating stomata to improve photosynthesis under FL conditions. However, both stomatal opening and stomatal density are likely to contribute to the changes of stomatal conductance under FL conditions, depending on the species/situation (Głowacka et al, 2018; Zhang, Kaiser, Marcelis, Yang, & Li, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The speed of the photosynthetic induction in light flecks can be reduced by nitrogen deficiency [ 34 ], indicating that the plant nutrition directly influences the leaf physiology under fluctuating light conditions. Salinity stress may reduce plant growth and photosynthesis to a greater degree under the conditions of fluctuating light than under conditions of homogeneous light [ 35 ]. Global change conditions of elevated CO 2 may enhance the photosynthesis and growth of plants to a greater degree under the conditions of fluctuating light than under the conditions of uniform irradiance [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher proliferation of roots was observed in ET101-inoculated plants with increased lateral root formation and growth (data not shown), thereby allowing better penetration into the soil to acquire water and nutrition. Salt stress is known to cause damage to the chloroplast structure and instability of the chlorophyll protein complexes resulting in decreased chlorophyll content of leaves (Parida and Das, 2015;Zhang et al, 2020). Although this is true for uninoculated tomato and rice plants, the inoculated plants accumulated greater amounts of photosynthetic pigments (chlorophyll and carotenoids).…”
Section: S Sciuri Protected Tomato and Rice Plants From Salinity Injurymentioning
confidence: 99%
“…Decrease in intracellular CO 2 concentration and photosynthesis during salinity stress due to stomatal closure leads to lesser availability of CO 2 to the RuBisCO enzyme binding, thereby enhancing the rate of photorespiration (Igamberdiev, 2015). Salinity stress-induced accumulation of excess salts is known to affect the function of photosystems by modulating the photosynthetic proteins in chloroplasts causing irreversible damage to the photosynthetic apparatus at all developmental stages in glycophytic plants (Sun et al, 2016;Li et al, 2019;Rodríguez-Ortega et al, 2019;Zhang et al, 2020). Adaptation of plants to salinity stress involves modification of complex physiological traits, metabolic pathways, and gene networks (Nounjan et al, 2012;Gupta and Huang, 2014;Ghorbani et al, 2018;Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%